2021
DOI: 10.1093/mnras/stab2956
|View full text |Cite
|
Sign up to set email alerts
|

Constraining cosmology with a new all-sky Compton parameter map from the Planck PR4 data

Abstract: We constructed a new all-sky Compton parameter map (y-map) of the thermal Sunyaev-Zel’dovich (tSZ) effect from the 100 to 857 GHz frequency channel maps delivered within the Planck data release 4. The improvements in terms of noise and systematic effects translated into a y-map with a noise level smaller by ∼7 per cent compared to the maps released in 2015, and with significantly reduced survey stripes. The produced 2020 y-map is also characterized by residual foreground contamination, mainly due to thermal du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…first step towards using the full potential of small-scale CMB data. We then combine the SPT high-data with the Planck21-tSZ power spectrum (Tanimura et al 2022) to further constrain cosmological and scaling relation parameters. This combination does improve constraints but mostly shifts the best-fit parameters towards smaller values of Ω m , and σ 8 (from 0.38 and 0.82 to 0.35 and 0.77, respectively), in better agreement with Planck CMB data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…first step towards using the full potential of small-scale CMB data. We then combine the SPT high-data with the Planck21-tSZ power spectrum (Tanimura et al 2022) to further constrain cosmological and scaling relation parameters. This combination does improve constraints but mostly shifts the best-fit parameters towards smaller values of Ω m , and σ 8 (from 0.38 and 0.82 to 0.35 and 0.77, respectively), in better agreement with Planck CMB data.…”
Section: Discussionmentioning
confidence: 99%
“…The inverse Compton effect of CMB photons on energetic electrons from hot gas in galaxy clusters and groups (and thus filaments) is responsible for the tSZ anisotropies and additional power at small scales in the angular power spectrum of CMB fluctuations. Such an effect is frequency-dependent, a property which allows one to separate tSZ signal from other components in CMB data and reconstruct both a tSZ map (Planck Collaboration XXI 2014;Planck Collaboration XXII 2016;Aghanim et al 2019;Madhavacheril et al 2020;Bleem et al 2022;Tanimura et al 2022) and power spectrum (Planck Collaboration XXI 2014;Planck Collaboration XXII 2016;Tanimura et al 2022). The power spectrum amplitude and shape of this secondary anisotropy are highly dependent on the number of halos and their distribution in mass and redshift, and thus on the cosmological model considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use a version of the publicly available Monte-Carlo Markov chain sampler CosmoMC (Lewis & Bridle 2002;Lewis 2013), modified to include the SPT likelihood, available online (Reichardt et al 2021), and the Planck21-tSZ likelihoods, based on Tanimura et al (2022) data and following Salvati et al (2018). We further modify the sampler to allow for an on-the-fly RF-prediction of the tSZ, patchy kSZ and late-time kSZ angular power spectra (see above and Appendix A), as initiated in Paper I.…”
Section: Mcmc Analysismentioning
confidence: 99%
“…While our simulations predict a higher power compared to the values reported by ACT, Planck, and SPT, the power spectrum is in good agreement with the publicly available bahamas 1 simulations (McCarthy et al 2017(McCarthy et al , 2018 shown as the orange solid curve. We show the measured values by ACT (Dunkley et al 2013) as blue triangle, Planck (Tanimura et al 2022) as yellow diamonds, SPT-SZ (George et al 2015) as green square, and the combination of SPT-SZ and SPTpol (Reichardt et al 2021) as red circle. The fiducial bahamas model shown here includes astrophysical feedback which pushes the gas out from the haloes reducing the power on small-scales compared to the case without feedback effects (Shaw et al 2010;McCarthy et al 2014).…”
Section: Thermal Sz Simulationsmentioning
confidence: 99%